The value analysis of tumor deposit in the comprehensive evaluation before differentiated thyroid cancer RAI therapy - Wang, Lei; Yang, Jing; Zhu, Yuan; Li, Zhiyong (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to investigate the impact of tumor deposit (TD) on Radioiodine (RAI) therapy efficacy in Differentiated Thyroid Cancer (DTC) and explore their potential role in postoperative staging and the American Thyroid Association (ATA) initial risk stratification system before RAI treatment.MethodsThis study retrospectively analyzed data from a total of 11,278 thyroid cancer surgical patients between 2019 and 2023. Among 2,162 patients were considered eligible for prognostic analysis (2056 cases in the TD-negative group, 106 cases in the TD-positive group). A 1:1 propensity score matching was conducted for the TD-positive group. Single-factor and multiple-factor analyses of prognostic factors were performed for both groups. The predictive abilities of different N stages, TNM staging, and the ATA initial risk stratification system including TD were evaluated.ResultsThere were 235 cases (2.08%) of TD-positive patients. Multivariate analysis demonstrated that gender, presence of TD, the ATA initial risk stratification system, and TNM staging were independent prognostic factors. In all patients, those in the N1a stage, TNM stage I, and ATA intermediate risk group, the cumulative incidence of ER in the TD-positive group was lower than that in the TD-negative group (48.6% vs. 77.8%, 37.5% vs. 78.7%, 35.4% vs. 67.4%; P = 0.019, 0.001, 0.013 respectively). Patients with TD-positive in N1a stage had no significant difference in prognosis compared to TD-negative patients in N1b stage (32.6% vs. 42.6%, P = 0.867); TD-positive patients in TNM stage I had similar prognosis to TD-negative patients in TNM stage II (37.5% vs. 28.9%, P = 0.338); TD-positive patients in the ATA intermediate risk group showed no significant difference in prognosis compared to TD-negative patients in the ATA high risk group (35.4% vs. 12.5%, P = 0.300).ConclusionTD should be considered as a prognostic factor in the postoperative RAI treatment. We propose incorporating TD into the TNM staging and the ATA initial risk stratification system as a reference, suggesting that TD-positive patients in N1a stage be classified as N1b stage; patients in TNM stage I be classified as TNM stage II ;and the ATA intermediate risk patients be classified as the ATA high risk.